(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article explores practical and effective steps for designing a well-structured reading unit using any type of text in the context of teaching reading skills. It highlights the importance of selecting appropriate materials, establishing clear learning objectives, and integrating pre-reading, while-reading, and post-reading activities. The paper emphasizes communicative, interactive, and learner-centered approaches aligned with modern methodology. Through these steps, educators can enhance reading comprehension, vocabulary development, critical thinking, and overall language proficiency. The article aims to support teachers in creating adaptable, engaging, and pedagogically balanced reading units suitable for various learner levels.